Rancang Bangun Sistem Kontrol Dan Monitoring Smart Aquaponic Menggunakan Firebase Dan IoT - Yusuf, Muhammad; Ferdinand Hafith, Daniel; Farid Faqih, Muhammad; Pramono (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
Aquaponics is a cultivation system that combines aquaculture (fish farming) and hydroponics (soil-less plant cultivation) in an integrated environment. To enhance the efficiency and effectiveness of aquaponic systems, technology is needed that can automatically and in real-time monitor and control various environmental parameters. This research aims to design and build a smart aquaponic control and monitoring system using Firebase and Internet of Things (IoT) technology. The system utilizes sensors to measure crucial parameters such as water pH, temperature, and dissolved oxygen levels. Data from these sensors are sent to the Firebase platform via IoT connections, enabling remote monitoring and control through a web-based application. Test results show that the developed system is capable of providing real-time data and issuing automatic notifications if any parameters are outside optimal ranges. The implementation of this system is expected to improve the productivity and sustainability of aquaponics by facilitating efficient management and maintenance.